(untitled) (International Journal of Architecture and Urbanism, 2025)
In the several production forest areas on Java island, there are groups of people who live in these areas. They are known as magersari or magersaren. One of the Magersaren settlements is located at Boro Sumbersari hamlet, Tawangargo village, Karangploso, Malang Regency. The area is specifically located in the UB Forest Education and Training area. Unfortunately, like in other places, the Magersaren there lives in inadequate housing buildings. Several things keep them in this situation. Besides the regulation that applies in this zone, the financial situation also becomes a burden. Thus, a feasible residential design concept is needed following the needs of Magersaren settlers and according to the regulations. This research runs qualitatively with a deductive approach. The design concept used the ‘Kampung Srotongan’, one of the Javanese house types which have been built long ago in this area. The concept of the houses is designed with a pragmatism paradigm. From the analysis, four models adjusted to the number of magersaren’s family members. The model uses a modular house concept that is supported by a semi-permanent structural system. The combination of natural (local) and fabricated materials in the model considered improving the effectiveness and efficiency of the development process, especially in inviting CSR programs to get involved.